Automatic whiteboard cleaner - Nor Farah Zahreen Binti Maidin (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2014)
Whiteboard had been used widely in the schools and universities. Unluckily, the whiteboard always left unclean, as the teachers need rush to the next class since it need to be clean manually. As a result, this project had been introduced to solve this problem. The automatic whiteboard cleaner is the project that based on the hardware and software. This is a machine, which can clean a whiteboard with a single press of a button. The duster bar that made from aluminum will move from left to right. The automatic whiteboard cleaner will be supported by DC motor to ensure the duster bar is moving. Besides, two limit switches are used to detect boundaries of the whiteboard. So when the duster bar touches the limit switches, it will stop moving and return to original position. A PIC18F4580 microcontroller that is programmed in C language is the main part of this machine. The AutoCAD software is used to design the whiteboard prototype only then the prototype is fabricated while MPLAB is used to run the microcontroller program. The advantages of this machine is it only use a DC motor and takes shorter time to clean the whole whiteboard.